Cluster randomised controlled trial to determine the effect of peer delivery HIV self-testing to support linkage to HIV prevention among young women in rural KwaZulu-Natal, South Africa: a study protocol - Maryam Shahmanesh; Janet Seeley; Nondumiso Mthiyane; Natsayi Chimbindi; Jaco Dreyer; Theresa Smit; Carina Herbst; Paul Mee; Oluwafemi Atanda Adeagbo; Melissa Neuman; Nonhlanhla Okesola; Cheryl Johnson; et al. (BMJ Open, 2019)
Introduction A cluster randomised controlled trial (cRCT) to determine whether HIV self-testing (HIVST) delivered by peers either directly or through incentivised peer-networks, could increase the uptake of antiretroviral therapy and pre-exposure prophylaxis (PrEP) among young women (18 to 24 years) is being undertaken in an HIV hyperendemic area in KwaZulu-Natal, South Africa.Methods and analysis A three-arm cRCT started mid-March 2019, in 24 areas in rural KwaZulu-Natal. Twenty-four pairs of peer navigators working with ~12 000 young people aged 18 to 30 years over a period of 6 months were randomised to: (1) incentivised-peer-networks: peer-navigators recruited participants ‘seeds’ to distribute up to five HIVST packs and HIV prevention information to peers within their social networks. Seeds receive an incentive (20 Rand = US$1.5) for each respondent who contacts a peer-navigator for additional HIVST packs to distribute; (2) peer-navigator-distribution: peer-navigators distribute HIVST packs and information directly to young people; (3) standard of care: peer-navigators distribute referral slips and information. All arms promote sexual health information and provide barcoded clinic referral slips to facilitate linkage to HIV testing, prevention and care services. The primary outcome is the difference in linkage rate between arms, defined as the number of women (18 to 24 years) per peer-navigators month of outreach work (/pnm) who linked to clinic-based PrEP eligibility screening or started antiretroviral, based on HIV-status, within 90 days of receiving the clinic referral slip.Ethics and dissemination This study was approved by the Institutional Review Boards at the WHO, Switzerland (Protocol ID: STAR CRT, South Africa), London School of Hygiene and Tropical Medicine, UK (Reference: 15 990–1), University of KwaZulu-Natal (BFC311/18) and the KwaZulu-Natal Department of Health (Reference: KZ_201901_012), South Africa. The findings of this trial will be disseminated at local, regional and international meetings and through peer-reviewed publications.Trial registration number NCT03751826; Pre-results.